Kale (Brassica oleraceaL. var. acephala) as a source of dietary fibre - Maciejak, Aleksandra; Kosmala, Monika (Biotechnology and Food Science, 2019)
The aim of the work was to determine dietary fibre content (total, soluble and insoluble) in kale. Packages of the vegetable were bought in local stores in Lodz. Dietary fibre content determined during the research was compared with the information given by producers. C onducted research proved that kale is rich in dietary fibre ( from 4 .36 to 5.05 g per 100 g of product in fresh weight, mostly in form of insoluble dietary fibre). The results of determinations carried out in the laboratory co incide with the data declared by the producers.